Long interspersed nuclear elements safeguard neural progenitors from precocious differentiation - Toda, Tomohisa; Bedrosian, Tracy A.; Schafer, Simon T.; Cuoco, Michael S.; Linker, Sara B.; Ghassemzadeh, Saeed; Mitchell, Lisa; Whiteley, Jack T.; Novaresi, Nicole; McDonald, Aidan H.; Gallina, Iryna S.; Yoon, Hyojung; et al. (Cell Reports, 2024)
Long interspersed nuclear element-1 (L1 or LINE-1) is a highly abundant mobile genetic element in both humans and mice, comprising almost 20% of each genome. L1s are silenced by several mechanisms, as their uncontrolled expression has the potential to induce genomic instability. However, L1s are paradoxically expressed at high levels in differentiating neural progenitor cells. Using in vitro and in vivo techniques to modulate L1 expression, we report that L1s play a critical role in both human and mouse brain development by regulating the rate of neural differentiation in a reverse-transcription-independent manner.
CRIS-Team Scopus Importer:2024-02-23
Keywords: brain development; CP: Developmental biology; CP: Neuroscience; L1; LINE-1; neural progenitor cells; repetitive elements